On certain species of the genus Phyllium Illiger, 1798, with proposals for an intra-generic systematization and the descriptions of five new species from the Philippines and Palawan (Phasmatodea: Phylliidae: Phylliinae: Phylliini) - Hennemann, Frank H.; Conle, Oskar V.; Gottardo, Marco; Bresseel, Joachim (Zootaxa, 2009)
Thirteen species of Phyllium (Phyllium) Illiger, 1798 are studied and (re)described in detail with emphasis on those species which exhibit more or less well developed alae in the females and those occurring in the Philippine Islands and on Palawan. Amongst these five new species are described and illustrated from both sexes and the eggs: Ph. (Ph.) ericoriai Hennemann, Conle, Gottardo & Bresseel n. sp. from the Philippine Islands of Luzon, Marinduque and Batan, Phyllium philippinicum Hennemann, Conle, Gottardo & Bresseel n. sp. from the Philippine Island of Luzon, Phyllium mindorense Hennemann, Conle, Gottardo & Bresseel n. sp. from the Philippine Island of Mindoro, Phyllium mabantai Bresseel, Hennemann, Conle & Gottardo n. sp. from the Philippine Island of Mindanao and Ph. (Ph.) gantungense Hennemann, Conle, Gottardo & Bresseel n. sp. from Palawan. Ph. (Ph.) celebicum de Haan, 1842 is re-described with the male and egg described and illustrated for the first time. It is shown to be restricted to Sulawesi and Ambon with all records from continental Asia based on misidentifications mostly relating to Ph. (Ph.) westwoodii Wood-Mason, 1875. All Philippine records of Ph. (Ph.) celebicum de Haan relate to Ph. (Ph.) ericoriai Hennemann, Conle, Gottardo & Bresseel n. sp.. Both sexes and the eggs of Ph. (Ph.) westwoodii Wood-Mason, 1875 are re-described and illustrated and a survey is provided of its intraspecific variability. This species was misinterpreted by most former authors and is here shown to be widely distributed in southern continental Asia having so far been recorded from the Andamans, Myanmar, Thailand, Laos, Kamputchea, S-China, N-Vietnam, Sumatra and the Riouw Archipelago. The holotype of Phyllium (Ph.) siccifolium (Linné, 1758) is described in detail for the first time with illustrations provided. This, the type-species of the entire family Phylliidae, is shown to have been misinterpreted by almost all previous authors and the distribution to be in fact restricted to the Moluccas (Ambon, Ceram, Halmahera, Sula Islands and Banggai). Ambon is shown to be most likely the type-locality of Ph. siccifolium. Records from Peninsular Malaysia have proven to relate to Ph. (Ph.) hausleithneri Brock, 1999 and Philippine material erroneously referred to as “Ph. siccifolium” by various authors is Ph. (Ph.) philippinicum Hennemann, Conle, Gottardo & Bresseel n. sp.. Ph. (Ph.) tobeloense Größer, 2007 from Halmahera (Moluccas) is shown to represent a junior synonym of Ph. siccifolium (n. syn.). Comparison of the Malayan Ph. (Ph.) hausleithneri Brock, 1999 with Malayan specimens previously referred to as „Ph. siccifolium” has revealed these to be the same species which shows considerable variation concerning to the shape of the abdomen in females. Ph. (Ph.) hausleithneri is characteristic for the conspicuous blue interior marking on the mesoand metacoxae. Both sexes and the eggs as well as the remarkable variation of females are illustrated. Similarly strong variation is recorded and illustrated for females of the Javanese Ph. (Ph.) jacobsoni Rehn & Rehn, 1933. A brief discussion of its variability and distribution as well as a summary of the diagnostic features and illustrations of the females and eggs are presented. The Philippine Ph. (Ph.) bilobatum Gray, 1843 is only known from the unique female holotype and all subsequent records appear to have been based on misidentified material. Subsequent records from Peninsular Malaysia relate to Ph. (Ph.) hausleithneri Brock, 1999 and records from Java have all proven to represent Ph. (Ph.) jacobsoni Rehn & Rehn, 1933. The male allotype of Ph. (Ph.) woodi Rehn & Rehn, 1933 from the Philippine island of Mindanao is specifically distinct from the female holotype from Sibuyan Island and here designated as a paratype of Ph. (Ph.) mabantai Bresseel, Hennemann, Conle & Gottardo n. sp.. The diagnostic features of Ph. (Ph.) woodi, a species so far only known from the island of Sibuyan, are briefly summarized. With emphasis on the Philippine fauna, a checklist and keys are provided for the nine species of Phyllium Illiger, 1798 presently known to occur in the Philippine Islands and Palawan. Critical notes are presented on the current intra-generic systematization of Phyllium Illiger, 1798 along with an extended and more detailed distinction between the two subgenera contained, Phyllium Illiger, 1798 and Pulchriphyllium Griffini, 1898. Based on morphological features of the insects and eggs species-groups are suggested within both subgenus. Phyllium (Phyllium) is proposed to include the siccifolium species-group and celebicum species-group, whereas Phyllium (Pulchriphyllium) subdivides into the bioculatum species-group, schultzei species-group, frondosum species-group and brevipenne species-group. The latter two groups are shown to differ considerably from other members of the subgenus and do not belong in Pulchriphyllium (sensu stricto). Keys are provided for the distinction of the speciesgroups here proposed. The celebicum species-group of Phyllium (Phyllium) is discussed in more detail and provisionally contains all those species in which females have developed alae, a fact overlooked for several species by previous authors. Eight species are here attributed to the celebicum species-group and keys are provided to distinguish these.Five species are transferred from one subgenus to the other. Phyllium drunganum Yang, 1995 and Ph. tibetense Liu, 1993 from S-China are removed from the subgenus Pulchriphyllium and transferred to Phyllium (Phyllium) (n. comb.). Ph. chitoniscoides Größer, 1992 and Ph. frondosum Redtenbacher, 1906 from New Guinea as well as Ph. keyicum Karny, 1914 from they Key-Islands are removed from Phyllium (Phyllium) and transferred to the frondosum species-group of Phyllium (Pulchriphyllium) (n. comb.). Ph. insulanicum Werner, 1922 from the Key Islands is removed from synonymy with the New Guinean Ph. frondosum Redtenbacher, 1906 and synoynmised with Ph. keyicum Karny, 1914; differences between Ph. frondosum and Ph. keyicum are presented. The Philippine Phyllium (Phyllium) pusillulum Rehn & Rehn, 1933 is removed from the genus Phyllium Illiger, 1798 and transferred to Microphyllium Zompro, 2001, hence the valid name now is Microphyllium pusillulum (Rehn & Rehn, 1993 n. comb.). Some taxonomically important features traditionally used for distinguishing the genera and species in the family Phylliidae are critically discussed. The present distinction of Chitoniscus Stål, 1875 and Phyllium Illiger, 1798 is shown to be problematic since research on the length relation of the meso-praescutum (anterior portion of the mesonotum in front of the tegmina) has revealed several species in Phyllium Illiger, 1798 that violate the generic description by having this clearly transverse and actually keying out to Chitoniscus Stål, 1875. The prosternal projection characteristic for Chitoniscus Stål, 1875 is shown to be also present in several members of Phyllium Illiger, 1798. Although the entire family Phylliidae was traditionally diagnosed by females having the antennae with nine segment, six species of Phyllium (Phyllium) Illiger, 1798 are here shown to have in fact ten antennomeres. Another interesting fact are the distinctly pectinate ungues (= claws) seen in Ph. (Ph.) gantungense n. sp. which have so far only been known to occur in the Old World areolate family Aschiphasmatidae.